Challenges to the Labor Market Institutions in the Area of Supporting NEETs - Sylwia Saczynska-Sokol (Institute of Economic Research (IER), 2017)
Various and complicated reasons for belonging to the NEET category, resulting largely from young people's personal and family circumstances, cause that the activation programmes undertaken by public employment services, both in the professional and educational sphere, prove inadequate. Despite the fact that labour market instruments dedicated to young people represent a wide range of possibilities for supporting them in combating professional and educational inactivity, the background of their problems requires new actions that should be undertaken by labour market institutions and their partners. Taking the above into consideration, the aim of this study is to identify the challenges faced by the public employment services and other labour market institutions in the area of activating youth experiencing the most difficult situation in the labour market. The article is based partly on the results of quantitative and qualitative research, conducted in the framework of the project implemented by the Provincial Labour Office in Bialystok Podlasie open to young people, financed by Operational Programme Knowledge Education Development (PO WER). The results of the study have led to the identification of necessary actions which should be undertaken by labour market institutions to support young people representing the NEET generation. These actions can be classified into different categories. They include preventing inclusion into the NEET group, developing the most effective solutions in the area of getting in touch with this group of young people and supporting them as well as creating a culture of cooperation for their benefit. The study has also revealed the need to carry out in-depth research of the NEET population.
Keywords: R23; 330; labor market; labor market institutions; public employment services; NEETs